Steroid-refractory GVHD: T-cell attack within a vulnerable endothelial system - Luft, Thomas; Dietrich, Sascha; Falk, Christine; Conzelmann, Michael; Hess, Michael; Benner, Axel; Neumann, Frank; Isermann, Berend; Hegenbart, Ute; Ho, Anthony Dick; Dreger, Peter (Blood, 2011)
Acute graft-versus-host disease (GVHD) is a major complication of allogeneic stem cell transplantation (SCT) and can be readily controlled by systemic high-dose steroids in many patients. However, patients whose GVHD is refractory to this therapy have a poor prognosis. Refractory patients have ongoing end-organ damage despite effective immunosuppression with second-line regimens, suggesting pathomechanisms independent from the initiating T-cell attack. To explore whether endothelial damage might contribute to GVHD refractoriness and to study the role of angiopoietin-2 (ANG2) in this process, we have compared kinetics of T-cell activation markers and markers of endothelial dysfunction in the serum of patients with sensitive (n = 23) and refractory GVHD (n = 25). Longitudinal measurements of soluble FAS ligand along with other immune markers demonstrate that refractory patients are not exposed to an overwhelming or unresponsive T-cell attack. However, in contrast to sensitive GVHD, refractory GVHD was associated with rising thrombomodulin levels and high ANG2/ vascular endothelial-derived growth factor ratios. Patients with refractory GVHD showed significantly increased ANG2 levels already before SCT. These results suggest that endothelial cell vulnerability and dysfunction, rather than refractory T-cell activity, drives treatment refractoriness of GVHD and opens new avenues for prediction and control of this devastating condition.